Libertad de expresión y límites democráticos - José Luis Castro-Montero (Ius Humani. Jornal do direito, 2017)
There is a significant literature justifying why freedom of speech should be seen as a fundamental right. At the individual level, freedom of speech should be protected to further autonomy. In the public domain, freedom of speech is not only essential for the discovery of truth through the marketplace of ideas, but also fosters citizens’ checks over public officials. The present essay takes an alternative but at the same time integrative approach, by stating that freedom of speech is a necessary condition of political legitimacy and democratic equality. This is particularly important to understand the limits of freedom of speech, as certain laws forbidding free speech may also annihilate political legitimacy to enforce non-discriminatory regulation. In this regard, special laws that protect public officials defamation produce an unintended effect over dissident voices, as these laws exclude them from public debates. Conversely, legitimacy of non-discriminatory laws is justified when opinions are publicly expressed. Advancing this unintended effect of non-discriminatory regulation enforcement, this essay explores the close interdependency of public opinion, political legitimacy and democratic equality. Particularly the Ecuadorian case serves well to illustrate this viewpoint.